THE IMPROVEMENT OF MAINTENANCE SERVICE FOR TRACTION NETWORKS EQUIPMENT ON THE BASE OF PROCESS APPROACH - Mironov, D. V. (Science and Transport Progress, 2014)
Purpose. The new methods development for improving the maintenance service for equipment of traction networks in order to increase its efficiency and quality. Methodology. In world practice of solving problems related to the quality of products and services is usually achieved by introducing quality management system in to the enterprises. The provisions of quality management system were used for solving the problem. The technologies of process engineering were used for describing the main stages of maintenance service. Findings. The development of high-speed movement and growth of its intensity, the use of electric rolling stock of a new generation require the introduction of new methods diagnostics of equipment technical state and improvement of the existing maintenance system and repair of power supply. Developing a model of business-processes, their optimization with using techniques of process engineering and system management is needed for the transition to the management system based on the process approach. From the standpoint of the process approach and in accordance with the requirements of the quality management system (ISO 9001-2009), the operation of the E (Department of electrification and power supply) infrastructure sector is represented as a scheme of business-processes in which the guaranteed supply with electricity of railway and third-party consumers is defined as the main business-process of management. Each of the sub-process of power supply for consumers is described in details. The use methods and main stages of process approach for sample management system reorganization were investigated. The methodology and the application method of PDCA (Plan-Do-Check-Act) closed loop to the equipment maintenance system were described. The monitoring process of traction networks maintenance using the process approach was divided into components after investigations. The technical documentation of maintenance service was investigated in details. Ways to improve business-processes of E (Department of electrification and power supply) management were described. Originality. Maintenance improvement ways for equipment of traction networks using process engineering technologies and quality of electric power supply were proposed. Practical value. Using the provisions of the quality management system to the process of maintenance equipment will let ensure the improvement of process quality by increasing the reliability indices of electric equipment, the service level of consumers and changes of production processes focused on the efficiency increase of the sector activity.